Elderly-Onset Generalized Pustular Psoriasis without a Previous History of Psoriasis Vulgaris - Takayuki Aizu; Akinobu Matsui; Noriko Takiyoshi; Eijiro Akasaka; Takahide Kaneko; Hajime Nakano; Kazumitsu Sugiura; Masashi Akiyama; Daisuke Sawamura (Karger Publishers, 2015)
Generalized pustular psoriasis (GPP) is characterized by sudden fever and extensive erythema with pustules and occurs in patients with or without preceding psoriasis vulgaris. We report an 83-year-old man showing irregularly shaped erythema with pustules on the trunk and extremities. He initially had no fever and came to our clinic a few days after the onset of the skin lesions because of high fever and general malaise. We found an extension and new development of erythema and pustules on the whole body. The patient also manifested night delirium. Histological examination revealed neutrophil infiltration into the upper epidermis, which formed a spongiform pustule of Kogoj. Pustular fluid cultures were negative for bacteria. We diagnosed GPP without preceding psoriasis vulgaris. Mutation analysis revealed no significant mutations in IL36RN and CARD14. Previous reports indicated that onset of GPP at the age of 83 years is definitely rare. In older individuals, general disease characteristics include an atypical clinical course, an especially slow appearance and cure, and mental disorder. Our case also revealed such characteristics. Thus, it is necessary to be aware of the clinical course and mental problems in elderly patients with GPP.